Approximating Ukraine’s Laws to Those of the European Union Concerning Meat and Meat Products Cold Chain - RODIONOVA, Kateryna O.; STESHENKO, Volodymyr M.; YATSENKO, Ivan V. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020, 2020)
The main objectives of the research were such: to define the concept of cold chain as an object of legal regulation; to find out the content and features of the EU legislation on the safety and quality of meat and meat products during cold chain and its use in Ukraine; to characterize the legal bases of the current legislation of Ukraine on ensuring the safety and quality of meat and meat products during cold chain , to formulate proposals and recommendations aimed at improving the national legislation of Ukraine by approximating it to the EU legislation, which sets requirements for the safety and quality of meat and meat products throughout cold chain. To achieve the abovementioned objectives, the following methods were used: comparative legal, analytical, systemic, dialectical, generalizing, specific-search, structural-functional, semantic, methods of deduction and induction, etc. The content and features of the legal regulation of the safety and quality of meat and meat products in the current legislation of the European Union and Ukraine have been clarified. For the first time, the definition of the term 'cold chain' has been proposed by reference to it in author's editorial, which should influence its clearer scientific and practical understanding. It is determined that the temperature regimes of cold processing, storage and transportation of meat and meat products in Ukraine are regulated by a large number of legal acts, in particular: national standards of Ukraine (DSTU), technical regulations, technological instructions, rules of transportation, etc. It is found that national legal acts do not provide a systematic understanding of the particularities of cold chain legal regulation in the meat processing industry in order to ensure the safety and quality of meat and meat products. As a result of departmental inconsistency, the existing storage temperature parameters for the same product type in different legal acts differ from each other, which does not allow to determine the actual storage periods at different stages of the cold chain . In addition, current legal acts in Ukraine do not provide for constant monitoring of the temperature of cold-processed meat and meat products throughout all cold chain units and the hygienic condition of refrigerators throughout the shelf life. As a result, the cold chain is very difficult to be controlled and requires a large number of factors to be taken into account in order to bring safe and high-quality meat and meat products to the end consumer. According to the results of the research, proposals and recommendations are formulated to improve the national legislation of Ukraine governing the cold chain in the meat processing industry.